A model describing the effect of enzymatic degradation on drug release from collagen minirods - Metzmacher, Iris; Radu, Adrian Florin; Bause, Markus; Knabner, Peter; Friess, Wolfgang (European Journal of Pharmaceutics and Biopharmaceutics, 2007)
A drug delivery system, named minirod, containing insoluble non-cross-linked collagen was prepared to investigate the release of model drug compounds. To characterise the complete drug release process properly, a mathematical model was developed. Previously, a mathematical model describing water penetration, matrix swelling and drug release by diffusion from dense collagen matrices has been introduced and tested. However, enzymatic matrix degradation influences the drug release as well. Based on experimental data, a model was developed which describes drug release by collagenolytic matrix degradation based on enzyme diffusion, adsorption and cleavage. Data for swelling, collagen degradation and FITC dextran release from insoluble equine collagen type I minirods were collected. Sorption studies demonstrated a tight sorption of collagenase on collagen surfaces that follows a Freundlich sorption isotherm and results in a degradation constant of 3.8 × 10 mol/l for the minirods. The diffusion coefficients of FITC dextran 20 and 70 (3 × 10 and 2.4 × 10 cm/h) in water were analyzed by fluorescence correlation spectroscopy (FCS). Using these data, the mathematical model was verified by two-dimensional simulations. The numerical results agreed well with the measurements. © 2007 Elsevier B.V. All rights reserve
Keywords: Collagen; Enzymatic adsorption; Enzymatic degradation; FCS; Mathematical model; Numerical simulation